2019
DOI: 10.35313/ijabr.v1i02.75
|View full text |Cite
|
Sign up to set email alerts
|

Technology Adoption in Education-Based Business Services

Abstract: The objectives of this study are two folds. Firstly is to identify the advantages and disadvantages factors of electronic learning’s adoption. Secondly is to measure the influence of innovation adoption components toward users’ attitude in using electronic learning. A mixed method of study was carried out in response to the research’s objectives. The qualitative approach was conducted by means of interviewing 25 participants of users to identify e-learning advantages and disadvantages. The quantitative approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Nonetheless, the finding to the effect that experimentation negatively and insignificantly influenced e-learning implementation was contrary to the findings of previous scholars. For example, Al-Rahmi et al ( 2019), Kusdibyo et al (2019) and Ndongfack (2021) indicated that trialability (experimentation) had a strong impact on students' behavioural intention to use the e-learning system. Relatedly, Cao et al (2012) indicated that e-learning experimentation promoted the intrinsic motivation, learning quality, ability to resolve ill-structured problems and creative thinking ability of the students, thus enhancing e-learning.…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, the finding to the effect that experimentation negatively and insignificantly influenced e-learning implementation was contrary to the findings of previous scholars. For example, Al-Rahmi et al ( 2019), Kusdibyo et al (2019) and Ndongfack (2021) indicated that trialability (experimentation) had a strong impact on students' behavioural intention to use the e-learning system. Relatedly, Cao et al (2012) indicated that e-learning experimentation promoted the intrinsic motivation, learning quality, ability to resolve ill-structured problems and creative thinking ability of the students, thus enhancing e-learning.…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
“…There are several studies (Al-Rahmi et al, 2019;Cao et al, 2012;Daouk & Aldalaien, 2019;Kusdibyo et al, 2019;Lang et al, 2017;Ndongfack, 2021;Park et al, 2018;Pinho et al, 2021) that have examined the importance of experimentation in the implementation of e-learning. While the studies above show that scholars have made significant efforts to relate experimentation and e-learning implementation, contextual and empirical gaps emerged.…”
Section: Capabilities and E-learning Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…Boosted economies of various developed countries significantly influence countries’ projects with the eminent significance of elements ( Khan et al, 2016 ). Where the economies have been boosted from the projects with international importance, the countries could positively spend all possible amenities that the government retains for its public ( Kusdibyo et al, 2019 ).…”
Section: Literature Reviewmentioning
confidence: 99%